Inheritance and mapping of QTLs for Ascochyta blight resistance in chickpea (Cicer arietinum) - DIVYA LEKHI; AJINDER KAUR; UPASANA RANI; SANGEETA SOI; INDERJIT SINGH; SHAYLA BINDRA; ADITYA PRATAP; SARVJEET SINGH; C BHARADWAJ (The Indian Journal of Agricultural Sciences, 2022)
There are very limited studies on the QTLs governing Ascochyta blight resistance which is a major problem in chickpea (Cicer arietinum L.) grown in North West Plain Zone of India in the cooler climates and world over. An interspecific mapping population consisting of 157 F2:3 lines developed by crossing a resistant parent ILWC129 (C. reticulatum) with a susceptible variety GL769 (C. arietinum L.), was evaluated (2019–20) and genotyped (2021) for genetic studies and mapping of resistance to Ascochyta rabiei (syn. Phoma rabiei), isolate 8(3968). The inheritance pattern gave 1R:2H:1S goodness of fit ratio with χ2 value of 0.4 indicating that resistance against isolate 8 of the pathogen governed by a single gene. Out of 831 SSR markers screened, 86 were found polymorphic with 10.3% polymorphism from which only 41 markers segregated in 1:2:1 ratio and could be mapped. Eight linkage groups with a cumulative distance of 1042.31 cM were formed with an average distance of 25.42 cM. This is probably the first report of inheritance studies and tagging of A. rabei race 8 (arr8) resistance gene using molecular markers in an interspecific cross with C. reticulatum.